Answer:
6x² + 5x - 6
Step-by-step explanation:
Given
(2x + 3)(3x - 2)
Each term in the second factor is multiplied by each term in the first factor, that is
2x(3x - 2) + 3(3x - 2) ← distribute both parenthesis
= 6x² - 4x + 9x - 6 ← collect like terms
= 6x² + 5x - 6
Answer:
- 7, - 3, 1, 5
Step-by-step explanation:
Using the recursive rule and a₁ = - 7, then
a₂ = a₁ + 4 = - 7 + 4 = - 3
a₃ = a₂ + 4 = - 3 + 4 = 1
a₄ = a₃ + 4 = 1 + 4 = 5
The first four terms are - 7, - 3, 1, 5
Hi there I’m here for points I’m sorry I couldn’t help:/